Cupula response to otoconia debris in the semicircular canal - Santos, Carla F. (2021)
The vertigo symptoms are commonly related with inner ear diseases and it affects 20%-30% of the world population, and its prevalence increases with age. In this work, a three-dimensional computational model of the semicircular canal of the vestibular system, containing the fluids which promote the body balance, was used. The smoothed-particle hydrodynamics method was the computational process used to simulate the fluid behaviour, in which the elements are represented by particles and have constant mass. The other vestibular components were discretized using the finite element method. The movement performed to endolymph/cupula interaction analysis was reproduced in the simulation through the acquisition of the displacement field based on image analysis. The results obtained with the frames of the video recorded during the process is the appropriate method to simulate the real moves, due to the analysis of the region of interest located near the inner ear. The data obtained from the video acquisition were the input in the simulation with the semicircular model. The principal stress cupular response allowed to understand the interaction of the vestibular structures during a vertigo episode, and the influence of the otoconia in the cupula displacement. This model is the first step to improve the vestibular rehabilitation and the quality of life of patients suffering from vertigo.